The centrality of labor time in South African gold mining since 1886. (14th March 2016) - Stewart, Paul
Abstract: Labor time, as a dimension of South African mining labor history, has been ignored, both conceptually and historically. This article remedies this yawning gap by presenting primary and secondary evidence which demonstrates the centrality of labor time in South African gold mines since the discovery of gold in 1886. To this end, labor time is traced in two ways. Part I tracks industrial working time by tracing the length of the working day and week. Part II tracks the ever-increasing length of the African migrant labor contract. While industrial working hours remain remarkably stable for almost a century, the migrant labor contract systematically increases over a similar period. These two measures of labor time eventually coincide when the migrant labor system dissolves and black African workers take annual leave together with their compatriots across the racial divide. The explanation for the mining industry's long struggle to both maintain relatively long working hours and increasingly maximize the length of the migrant labor contract is construed as completing the received wisdom of Harold Wolpe's much celebrated and criticized `cheap- labor' thesis. (Wolpe, "Capitalism and Cheap Labor Power.")